The Effect of Return on Assets, Return on Equity, Current Ratio, and Debt to Equity Ratio on Stock Return on Coal Sub-Sector Companies Listed on the Indonesia Stock Exchange, 2017-2021 - Seldiah Rega Yhumita; Reswanda (Journal of World Conference (JWC), 2022)
Indonesia's economic growth requires substantial funding and investment to compete in the regional and global economy. Stock return is the level of profit obtained from stock investment. Stock return is significant for investors because it is one indicator to determine the success of an investment. Although several factors affect stock returns, this study only examined four variables: Return on Assets, Return on Equity, Current Ratio, and Debt to Equity Ratio. This study aimed to determine the effect of Return on Assets, Return on Equity, Current Ratio, and Debt to Equity Ratio on stock returns. The research population is 22 coal sub-sector companies on the Indonesian stock exchange in 2017-2021, and the chosen sample is 8 companies using the purposive sampling technique. The data analysis method used multiple linear regression with SPSS 20. The results showed that Return on Assets significantly negatively affected stock returns. Return On Equity has a significant positive effect on stock returns, the Current Ratio has no significant effect on stock returns, and the Debt-to-Equity Ratio has a significant negative effect on stock returns.